Concept of Islamic Education According to Walisongo - Abdul Azis Khoiri; Faldo Riski Al hidaya (Indonesian Journal of Education and Youth Development, 2026)
This research examines the concept of Islamic education according to Walisongo through a library research approach, by analyzing relevant literature about the methods of da'wah and education of each saint, such as Sunan Gresik who taught agriculture and built religious schools, and Sunan Ampel who pioneered inclusive Islamic boarding schools. The findings show that Walisongo applies a holistic and acculturative approach, integrating sharia, Sufism, local arts and culture (such as wayang, song and gamelan), as well as practical skills to spread Islam peacefully in the archipelago, including figures such as Sunan Bonang, Sunan Drajat, Sunan Kudus, Sunan Giri, Sunan Kalijaga, Sunan Muria, and Sunan Gunung Jati. The implication is that their educational model is relevant to be developed in the context of contemporary Islamic education in Indonesia in order to form a tolerant, adaptive and noble character.